Synthesis of n-Butylamine from Butyronitrile on Ni/SiO2: Effect of Solvent - Segobia, Dario Jobino (2014)
The effect of solvent on Ni(10.5%)/SiO2 activity and selectivity for the liquid-phase conversion of butyronitrile to butylamines was studied using ethanol, benzene, toluene and cyclohexane as solvents. In ethanol, a protic solvent, the Ni catalyst yielded n-butylamine (84%) and dibutylamine. Replacing ethanol by non-polar solvents (benzene, toluene, cyclohexane) caused significant changes in catalyst activity and selectivity. In particular, the selectivity to n-butylamine decreased at the expense of dibutylamine and tributylamine formation. The solvent effect on the catalyst performance was interpreted by considering: i) the solvent-catalyst interaction strength that was investigated by calorimetry, and temperature-programmed desorption of solvents characterized by mass spectrometry; ii) the solvent polarity and its ability for H-bond formation with n-butylamine.